Code-mixing Analysis on Narasi Newsroom with Cinta Laura Kiehl - Hani Elmahida; Berliana Islamiati; Endang Sartika (PRASASTI: Journal of Linguistics, 2023)
This research aimed to analyze the details of types, factors, and gestures that emerge through the utilization of code-mixing by Cinta Laura Kiehl in the Narasi Newsroom which talks about animal harassment in Indonesia. This is quite an attractive study because the subject of the research has mastered multi-language skills with an intercultural background. In addition, code-mixing is becoming a present-day lifestyle of language utilization in formal and informal cases. This is descriptive qualitative research that analyzed by code-mixing approach in sociolinguistics theory through the Cinta Laura’s answers utterance. The primary data were gathered by conducting video observation on YouTube and doing note-taking of the manuscript which consists of code-mixing. Moreover, the secondary data was collected from several books and journals that have been cited. This research found two code-mixing types commonly utilized; insertion type and congruent-lexicalization. Then, family, educational background, environments, and multi-language skills are measured as the main sociolinguistics factors that affect code-mixing. Moreover, during the show, there is co-gesture analyzed consciously emphasis while the subject said the different language to strengthen addressee comprehension.